2021
DOI: 10.3390/su13094885
|View full text |Cite
|
Sign up to set email alerts
|

Can Reflective Diary-Writing Increase Sufficiency-Oriented Consumption? A Longitudinal Intervention Addressing the Role of Basic Psychological Needs, Subjective Well-Being, and Time Affluence

Abstract: Sufficiency is a sustainability strategy aiming for (1) a decrease in absolute resource consumption on individual and societal levels, and (2) for socio-ecological justice and the fair distribution of costs and benefits of resource use to meet every human’s basic needs. This study examined a longitudinal intervention to foster individual sufficiency orientation (i.e., a multidimensional construct including both attitudes towards the sufficiency sustainability strategy and corresponding behavioral intentions). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Next to these cross-sectional studies, two online studies also used a longitudinal approach, measuring pro-environmental behavior at two or more time points and administering the intervention in between. Kesenheimer and Greitemeyer [22] examined whether daily text message appeals would increase pro-environmental donations and pro-environmental behavior on a multi-item self-report scale, and Tröger and colleagues [23] investigated the effect of reflective diary-writing on self-reported sufficiency-oriented behaviors.…”
Section: Valuable Null Resultsmentioning
confidence: 99%
“…Next to these cross-sectional studies, two online studies also used a longitudinal approach, measuring pro-environmental behavior at two or more time points and administering the intervention in between. Kesenheimer and Greitemeyer [22] examined whether daily text message appeals would increase pro-environmental donations and pro-environmental behavior on a multi-item self-report scale, and Tröger and colleagues [23] investigated the effect of reflective diary-writing on self-reported sufficiency-oriented behaviors.…”
Section: Valuable Null Resultsmentioning
confidence: 99%
“…The results showed that a sufficiency message emphasizing a dynamic norm had no particularly significant effects compared to the two other conditions. Furthermore, in a diary intervention study that aimed at increasing sufficiency orientation and consumption, it was shown that simply being part of the experiment increased participants' pro-sufficiency attitudes after a one-week diary intervention and remained at that level for four weeks thereafter (Tröger et al 2021). These studies indicate that businesses, which decide to promote sufficiency to their customers through advertising and communication efforts, might have only a limited impact on customer behavior.…”
Section: Limitations and Obstacles Of Sufficiency-promoting Communica...mentioning
confidence: 94%
“…Perhaps unsurprisingly, research also suggests that most of the strategies implemented to enable sufficiency-oriented consumption can be categorized as "shallow", as they focus primarily on knowledge and support, such as communication campaigns (e.g., Svenfelt et al 2022). These strategies have been shown to be inadequate in influencing intentions and decisions towards sufficiency-oriented behaviors, for example in online environments, where they are overshadowed by frequent pro-consumption advertisements (e.g., Frick et al 2021a;Tröger et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diary containing open questions about the process was used to record the participants' reflections on the intervention process. This qualitative tool is commonly used in mixed methods studies; it provides additional perspectives on data collected through other approaches (Cucu-Oancea, 2013), and it has been useful in recent research on increasing sustainable behaviour (see Tröger et al, 2021). Items in the diary included once-off tasks requesting students to describe the process of selecting interventions, record their impressions of the intervention week as a daily task, and indicate what they had learnt about reducing their EF as well as using an intervention for broader application.…”
Section: Reflective Diarymentioning
confidence: 99%